Reflections on the reform of multi-tiered sea use right in China - Yu, Minna; Yue, Xinkai (Frontiers in Marine Science, 2024)
As China’s marine economy continues to flourish, the scarcity of offshore marine space has become increasingly apparent. The establishment of multi-tiered sea use right in 2023 represents an effective solution to facilitate the scientific allocation and effective protection of marine resources, thereby promoting high-quality development of marine economy. This paper offers a comprehensive and analytical overview of China’s multi-tiered sea use right reform in the context of current status of ocean multi-use research and practice worldwide. China’s multi-tiered sea use is an innovative practice of ocean multi-use in western countries. This paper adopts the methods of literature analysis, normative analysis, empirical analysis and case study. On the basis of comparative analysis of multi-tiered sea use in China and ocean multi-use in western countries, benefits and challenges of China’s multi-tiered sea use right reform were summarized and analyzed, and suggestions from multiple perspectives are provided for implementing and developing multi-tiered sea use right in China.